2018
DOI: 10.1016/j.rbmo.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a score to predict ovarian response to stimulation in IVF

Abstract: This study aimed to integrate clinical and biological parameters in a score able to predict ovarian response to stimulation for IVF in gonadotrophin-releasing hormone (GnRH) antagonist protocols. A progressive discriminant analysis to establish a score including the main clinical and biological parameters predicting ovarian response was performed by retrospectively analysing data from the first ovarian stimulation cycle of 494 patients. The score was validated in a prospectively enrolled, independent set of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Thus, the present study utilized both AMH and basal FSH as markers of ovarian reserve. Consistent with our data, previous studies used basal FSH as the supporting factor for evaluating ovarian reserve 2324…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the present study utilized both AMH and basal FSH as markers of ovarian reserve. Consistent with our data, previous studies used basal FSH as the supporting factor for evaluating ovarian reserve 2324…”
Section: Discussionsupporting
confidence: 91%
“…The ability of AMH to predict the ovarian response to stimulation has been widely reported and numerous studies have shown good correlations between AMH and the ovarian stimulation index [26] or the number of collected oocytes in IVF [28] and thus has a good ability to diagnose high and poor responders [29,30]. In IUI, Freiesleben et al, using the same FSH dose (75UI) for all patients, have shown that the number of recruited mature follicles (18 mm) was dependent on the AMH levels [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian stimulation used a combination of recombinant FSH (Gonal F, Merck, Lyon, France or Puregon, MSD, Paris, France) and GnRH antagonist (Cetrotide 0.25 mg, Merck, Lyon, France or Orgalutran, MSD, Paris, France). The initial dose of FSH was chosen according the female age and the score described by Chalumeau et al [26]. Ovulation was triggered with recombinant hCG (Ovitrelle, Merck, Lyon, France) when at least one follicle ≥ 18 mm was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The predictive factors employed for the construction of the proposed algorithm were FSH, LH/FSH ratio, AMH, BMI, AFC and female age as well. Furthermore, the fact that this retrospective cohortbased model has been subsequently validated on a prospective fashion is an additional strength rendering this mathematical equation a powerful tool in the clinical practice (Chalumeau et al 2018).…”
Section: Predicting the Patients' Ability To Respond Adequately To Trmentioning
confidence: 99%
“…Following another direction in comparison to the models presented in Table 1, the La Marca and Broekmans studies attempted to predict ovarian response to different stimulation protocols (La Marca et al 2012;Broekmans et al 2014). Further to that, Moon and Chalumeau moved one step further by establishing distinct models which could predict the number of retrieved oocytes with a fair accuracy (Moon et al 2016;Chalumeau et al 2018). Apart from the above studies, Lewis assessed the fertilization rate according to male-related variables whereas Ashrafi calculated the OHSS risk chances among NPCOS women (Lewis et al 2004;Ashrafi et al 2015) Despite the predictive capacity of the abovementioned models, the weaknesses identified include the limitation of trial to other countries and clinics alongside those where they were developed and evaluated originally.…”
Section: Personalized Treatmentmentioning
confidence: 99%